الظروف المحتفة بالخطاب الشرعي وأثرها في تأويل النصوص - صايل أحمد أمارة (International Institute of Islamic Thought, 2016)
يناقش هذا البحث العلاقة بين الخطاب الشرعي والظروف المحتفة به حين صدوره، وأثر ذلك في تأويل النصوص، وقد ارتأينا تقسيمه إلى مبحثين، يتناول أولهما المقصود بالظروف المحتفة بالخطاب الشرعي، وطريقة الوقوف عليها، والفائدة من معرفتها، وبعض المسائل المتعلقة بالتأويل، ويتتبَّع ثانيهما بعض النماذج التطبيقية التي تشير إلى أنَّ الظروف المحتفة بالخطاب الشرعي هي من أدلة التأويل؛ ما يعني وجوب استحضارها في عملية الاجتهاد لكيلا يجافي الحكم المستنبط مقاصد المشرِّع. This article discusses the relationship between religious discourse and its surrounding circumstances and how such circumstances influence the issuing of rulings and the interpretation of religious texts.   The article is divided into two parts; the first deals with the meaning of the surrounding circumstances, the importance and benefits of their identification, and some issues related to interpretation. The second part provides some practical examples about how the circumstances surrounding religious discourse are considered evidence of interpretation. Accordingly, these circumstances should be taken into account in the process of Ijtihad, to ensure that the derived ruling is in line with the purposes (Maqasid) of Shariah.